Multiply Trauma in Children: Pulmonary Contusion does not Necessarily Lead to a Worsening of the Treatment Success - Goedeke, Jan; Boehm, Roland; Dietz, Hans-Georg (European Journal of Pediatric Surgery, 2014)
Aim The aim of the study is to evaluate the impact of pulmonary contusion on the overall outcome in children with multiply injury.Patients and Methods Retrospective review of 123 multiply injured children during a 10-year period (January 2000 to February 2010) who were admitted to the intensive care unit of a university affiliated, tertiary care pediatric trauma center. The diagnosis of pulmonary contusion (case group) was defined by the clinical context and the results of chest X-ray and blood gas analysis. Data were compared with a matched control group without the diagnosis of pulmonary contusion. Matching criteria were as follows: (1) age difference within 2 years; (2) sex; (3) similar injury pattern; (4) Pediatric Trauma Score (PTS) difference within 2 points; (5) Glasgow Coma Score (GCS) in two categories.Results The risk of pulmonary contusion must not be underestimated in multiply injured children. In our study, 49 of 123 patients (40%) showed signs of pulmonary contusion. A matched and pair analysis was performed in 46 patients (94%). Pulmonary contusion had an impact on the Pao2/ FIo2 ratio. It was significantly reduced in patients and caused insignificant extension of the ventilation time. Overall length of stay (LOS), LOS at pediatric intensive care unit, complication rate, mortality rate, and short-term outcome did not differ significantly between cases and controls.Conclusions Pulmonary contusion alters gas exchange but does not appear to increase morbidity and mortality of pediatric patients with multiply injury. Interpretation may be limited by sample size.
Keywords: multiple injured child; pulmonary contusion; short-term outcome